Bioformulation of Silk-Based Coating to Preserve and Deliver Rhizobium tropici to Phaseolus vulgaris Under Saline Environments - Mhada, Manal; Zvinavashe, Augustine T.; Hazzoumi, Zakaria; Zeroual, Youssef; Marelli, Benedetto; Kouisni, Lamfeddal (Frontiers in Plant Science, 2021)
Seed priming has been for a long time an efficient application method of biofertilizers and biocontrol agents. Due to the quick degradation of the inoculants or the primer, this technique has been limited to certain immediate uses. With the increase of awareness of the importance of sustainable use of biofertilizers, seed coating has presented competitive advantage regarding its ability to adhere easily to the seed, to preserve the inoculant and to decompose in soil. In this study we compare primed common bean seeds with R. tropici and Trehalose with coated seeds using a silk solution mixed with R. tropici and Trehalose. Through we represent the effect of priming and seed coating on seed germination and seedlings development by evaluating the above- and below-ground parameters under different salinity levels (0, 20, 50 and 75 mM). Results show that germination as well as morphological parameters have been significantly enhanced by the application of R. tropici and trehalose. Physiological response has been evaluated through the stomatal conductance, the chlorophyll content, and the total phenolic compounds. For all traits, R. tropici and trehalose help the plant to mitigate the negative impact of salt stress. These findings represent an important contribution to our understanding of stress responses in coated and primed seeds. This knowledge is essential to the design of coating materials optimized for stressed environments. However, further progress in this area of research must anticipate the development of coatings adapted to different stresses using micro and macro elements, bacteria, and fungi with a great focus on biopolymers for a sustainable agriculture and soil microbiome preservation.